Low and ultra-low anastomoses in combination to various variants of lymph node dissection in rectal cancer - S. N. Navruzov; S. B. Abduzhapparov; B. S. Navruzov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study potentials of simultaneous radical operations at rectal cancer with lymph node dissection and application of low and ultralow colorectal anastomoses.Material and methods. For 25 patients with cancer of the rectum radical surgery with lymph node dissection in D2 and D3 volume according to the level of tumor location was carried out. Reconstructive stage of operation was carried out with application of low and ultralow colorectal anastomoses by circular-stapler device of «Eticon» company. Results. No complications in postoperative period were marked. Term of observation was 1 year. No relapses and metastases were registered.Conclusions. Preliminary data allow to make conclusion on expediency of these types of operations with application of circular-stapler device and lymph node dissection.